Eksistensi Zikir Rateb Seuribee di Labuhanhaji dan Nilai-Nilai Karakter - Dedek Melda Imalia (Tadabbur: Jurnal Peradaban Islam, 2021)
This study was motivated by the phenomenon of the emergence of various dhikr (remembrance) gatherings that bring together many people who experience spiritual aridity. In Aceh, currently, there is a dhikr gathering that is well known for its work for the community called Rateb Seuribee dhikr. Rateb Seuribee dhikr is one of the dhikr gatherings that is in great demand within the community. In this study, the aim is to delve deeper into Rateb Seuribee dhikr by focusing on the existence of Rateb Seuribee dhikr and character values. The study used descriptive qualitative methods to obtain accurate and reliable data. Data were collected by means of interview and observation. The participants of the study consisted of the leaders, administrators, and the members of Rateb Seuribee dhikr. The results of the study indicated that Rateb Seuribee dhikr appeared to respond to the current condition of society which is experiencing spiritual aridity due to being lulled by worldly desires, leading them to drift away from the Creator. Taking into account such situations, Sheikh H. Amran Waly Al-Khalidi established a dhikr gathering named Rateb Seuribee dhikr. The people are mostly interested in following Rateb Seuribee dhikr in order to get peace of mind, get closer to Allah, improve characters, develop social attitudes towards fellow community members, forge closer ties of friendship between fellow citizens, and increase religious knowledge. In addition, the character values ​​obtained in carrying out Rateb Seuribee dhikr include religious, honest, disciplined, patient, sincere, enthusiastic, respectful, communicative, social care, responsible, and care for the environment.